Photobiomodulation therapy in third molar extraction complications (Research, Society and Development, 2022)
Alternatives have been studied to reduce pain, edema and greater non-post-operative tissue regeneration after the extraction of third molars. Photobiomodulation therapy (TFB) has been successfully used, besides having anti-inflammatory and analgesic action, it also has a local effect, accelerating tissue repair. The objective of this work is to present a case report using non-postoperative TFB of a patient who presented ecchymoses in the region of the palate originating from a fracture of the maxillary tuberosity, along with trismus and edema during the extraction of two third molars. Male patient, sought out the “Laser Therapy in Odontology” extension project from UFMA, 6 days after exodontia of two elements 18 and 48 with complaints of edema and lockjaw, without painful symptoms. Due to lockjaw that made adequate intraoral irradiation difficult, she was first performed with low-power extraoral laser irradiation. Subsequently, aiming to accelerate the drainage of liquids from the hemiface directly and as well as reduce the edema, it was carried out by irradiating the main lymph nodes. Intraoral irradiation with a low-power laser in the region of the sutures was performed 2 days after the 1st session in order to accelerate healing. After 6 sessions, there was a decrease in edema, an improvement in the mouth opening from 23 mm to 46 mm, in addition to the disappearance of the broken mucosa in the region of the tube, favoring healing, including in the region of the tooth 48, concluding that TFB with our parameters was effective. for the treatment of these complications in a reduced time.